COATING THICKNESS ANALYSIS OF DEPOSITED FeCrAl SUBSTRATE BY γ-AL2O3 THROUGH NiO-ELECTROPLATING - Hadi Pranoto; Nurato Nurato; Dafit Feriyanto (Universitas Mercu Buana, 2018)
Nickel Oxide (NiO) have widely applied in industrial and automotive to forming oxide layer on the substrate due to it have high thermal stability and corrosion resistant. However, NiO was not directly diffused to the substrate via co-precipitation, spray-pyrolysis and sol-gel methods. Therefore, NiO-electroplating was performed in coating FeCrAl substrate by γ-Al2O3 powder. This method was conducted using various time of 15, 30, 45, 60 and 75 minutes, a current of DC power supply is 1.28A and sulphamate type solution. From the data shows that smallest surface roughness (Ra) of NiO-electroplating (EL) samples located at EL 30 min sample for 0.69 µm. Ra of raw material was lower than coated samples due to it performed by coating activity on the substrate. It supported by coating thickness analysis that treated samples has a higher coating thickness up to 11.3 µm. EDS analysis observed some elements on coated and uncoated samples such as Carbon (C) of 4.62-20.67%, Oxygen (O) of 6.16-19.62%, Nickel (Ni) of 6.76-25.14%, Iron (Fe) of 23.96-48.53%, Sodium (Na) of 2.21-9.95%, Chromium (Cr) of 7.97-15.59% and Aluminum (Al) of 2.17-3.12%. Those elements promote to develop a protective oxide layer on FeCrAl at a high temperature of 1000 0C.